Deconstructing Cognitive Heterogeneity in Puerto Rican Spanish-Speaking Children With ADHD. (26th August 2020) - Nuñez, Alicia; San Miguel, Liza; Keene, Jennifer; Donohue, Bradley; Allen, Daniel N.
Abstract: Objective: There is limited understanding of the cognitive profiles of Spanish-speaking children with Attention-Deficit/Hyperactivity Disorder (ADHD). The current study investigated the cognitive cluster profiles of Puerto Rican Spanish-speaking children with ADHD using the Wechsler Intelligence Scales for Children-Fourth Edition Spanish (WISC-IV Spanish) Index scores and examined the association between cognitive cluster profiles with other potentially relevant factors. Method: Hierarchical cluster analysis was used to identify WISC-IV clusters in a sample of 165 Puerto Rican children who had a primary diagnosis of ADHD. To examine the validity of the ADHD clusters, analysis of variances and chi-square analyses were conducted to compare the clusters across sociodemographics (e.g., age and education), type of ADHD diagnosis (ADHD subtype, Learning Disorder comorbidity), and academic achievement. Results: Clusters were differentiated by level and pattern of performance. A five-cluster solution was identified as optimal that included (C1) multiple cognitive deficits, (C2) processing speed deficits, (C3) generally average performance, (C4) perceptual reasoning strengths, and (C5) working memory deficits. Among the five clusters, the profile with multiple cognitive deficits was characterized by poorer performance on the four WISC-IV Spanish Indexes and was associated with adverse sociodemographic characteristics. Conclusions: Results illustrate that there is substantial heterogeneity in cognitive abilities of Puerto Rican Spanish-speaking children with ADHD, and this heterogeneity is associated with a number of relevant outcomes.